Misbehavior online in higher education - Wankel, Laura A.; Wankel, Charles (Emerald, 2012)
As interaction in higher education among faculty, staff, students, and others becomes ever more digital, the welter of new online communication technologies have provided many unintentional opportunities for indiscipline and misconduct. As a result of this unfortunate increase is misbehavior, administrators and instructors in higher education are increasingly being called upon to remedy and forestall such actions. Misbehavior Online in Higher Education is rich in contemporary case studies, analytical reports, and up-to-date research providing detailed overviews of various misbehavior, including cyberbullying, cyberstaling, cyberslacking, and privacy invasion, hacking, cheating, teasing, and enhanced prejudicial attitudes. The development of approaches to addressing these problems is discussed and examples are provided. The book also anticipates emerging problematic behavior and the development of new policies, programs, facilities, and technologies to tackle the concerning behaviors is explored.
Includes index.
Keywords: Education -- Computers & Technology.; Education -- Higher.; Higher & further education, tertiary education.; Bullying & anti-bullying strategies.; Internet in higher education.; Education, Higher.; elektronické knihy; electronic books